Geronimo Stilton. Books 22 & 24 [compact disc, unabridged] - Stilton, Geronimo (Scholastic Audiobooks, 2011)
Presents books twenty-two and twenty-four in the Geronimo Stilton adventure series in which Geronimo is mouse-napped by his old friend Creepella von Cacklefur, and finds himself at Niagara Falls with his nephew Benjamin's class, who are determined to send him over the Falls in a barrel.